Development Of The International Social Entrepreneurship Institute Through Propaganda And Education Mechanisms; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Kuznetsova S. Svetlana; Kuznetsov V. Vladimir; Rebrova N. Natalia; Galtseva (Gal’tseva) O. V. Olga Valerievna; Odnokopylov I. G. Ivan Georgievich; Kutsenko E. Ekaterina (2018, 2018)
Title screen